Exploring the Antioxidant Potential of Teucrium Polium Extracts by HPLC-SPE-NMR and On-lineRadical-scavenging Activity Detection - Goulas, Vlasios; Gomez-Caravaca, Ana María; Exarchou, Vassiliki; Gerothanassis, Ioannis P.; Segura-Carretero, Antonio; Gutiérrez, Fernandez (My University, 2012)
Teucrium polium is a popular medicinal plant that is used in the daily diet and the in vitro and in vivo antioxidant potency of its extracts has been widely investigated. In the present work, polar extracts from T. polium were analyzed in terms of its composition and radical-scavenging activity with the employment of the state-of-the-art HPLC-SPE-NMR and HPLC-DPPH techniques in the search of new antioxidant agents for food industry. NMR and MS data revealed the presence of phenylpropanoid glycosides verbascoside and poliumoside, the flavones apigenin and its derivatives and two methoxyflavones. The on-line DPPH experiments showed that poliumoside is the most active component of the extracts and the antioxidant potential of T. polium polar extracts is mainly attributed to phenylpropanoid glycosides (66-80%). Our results suggested that T. polium extracts could be a promising source of natural antioxidants. This holistic approach also revealed that poliumoside or polar extracts of T. polium can be used in food industry as antioxidant agents with natural origin. The HPLC-SPE-NMR and HPLC-DPPH analysis of the extracts was performed for first time in the same device without any modification of the instrumentation, avoiding the need for isolation of the individual components.
Keywords: Flavonoids; HPLC-DPPH; HPLC-SPE-NMR; Phenylpropanoid glycosides; Plant extracts; Radical-scavenging activity